PHONICS VIDEO INSTRUCTION IN DEVELOPING THE SKILLS OF KINDERGARTEN PUPILS ON NAMING AND SOUNDING OF LETTERS: PHONICS VIDEO INSTRUCTION IN DEVELOPING THE SKILLS OF KINDERGARTEN PUPILS ON NAMING AND SOUNDING OF LETTERS - Balauag, Jenylyn (International Journal of Arts, Sciences and Education, 2022)
This Action Research was conducted to determine the effectiveness of Phonics Video Instruction in Developing Skills of Kindergarten Pupils on Naming and Sounding of Letters in Mambacag Elementary School, Tuao East District for School Year 2020-2021. This research utilized the kindergarten pupils of which 18 were male and 13 were female. The researcher used total enumeration in choosing the participants of the study. Quasi-Experimental particularly One-Group Pretest and Posttest Research Design was administered to one group of participants utilizing the pretest and posttest scores as the main source of data. The results of the study showed that there is an increase in the posttest as compared with the pretest scores. This implies that the intervention used in this study had caused significant difference in the mean scores. The Cohen’s d value also revealed that the intervention had caused huge effect in improving the reading skills of the participants. This only shows that the intervention is effective enough in effecting change in the performance of pupils as reflected by the significant difference in the mean posttest compared to that of mean pretest. It is therefore recommended that teachers may consider the implementation of Phonics Video Instruction in their respective classes to improve their pupils’ performance on naming and sounding of letters. It is also highly recommended that School Heads may consider the findings of this study in crafting programs and projects in their respective schools. Keywords: Phonics Video Instruction, Pretest and Posttest, Sounds, Alphabet, Phoneme